2004
DOI: 10.1242/dev.00935
|View full text |Cite
|
Sign up to set email alerts
|

Tcf3: a transcriptional regulator of axis induction in the early embryo

Abstract: The roles of Lef/Tcf proteins in determining cell fate characteristics have been described in many contexts during vertebrate embryogenesis, organ and tissue homeostasis, and cancer formation. Although much of the accumulated work on these proteins involves their ability to transactivate target genes when stimulated by β-catenin, Lef/Tcf proteins can repress target genes in the absence of stabilized β-catenin. By ablating Tcf3 function, we have uncovered an important requirement for a repressor function of Lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
233
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(242 citation statements)
references
References 51 publications
9
233
0
Order By: Relevance
“…3E). Furthermore, we found that canonical Wnt signaling is specifically activated in the prefusion epithelia and in the underlying mesenchyme in the medial nasal, lateral nasal, and maxillary processes, as demonstrated by expression of the specifically responsive TOPGAL transgene (DasGupta and Fuchs, 1999;Merrill et al, 2004;Ryan et al, manuscript submitted, Fig. 3F).…”
Section: The Wnt Pathwaymentioning
confidence: 71%
“…3E). Furthermore, we found that canonical Wnt signaling is specifically activated in the prefusion epithelia and in the underlying mesenchyme in the medial nasal, lateral nasal, and maxillary processes, as demonstrated by expression of the specifically responsive TOPGAL transgene (DasGupta and Fuchs, 1999;Merrill et al, 2004;Ryan et al, manuscript submitted, Fig. 3F).…”
Section: The Wnt Pathwaymentioning
confidence: 71%
“…Given the vast experience of numerous investigators employing inhibitory mutants of Tcf/Lef factors to modulate activity of the pathway in model systems from Drosophila melanogaster to mammalian cells (9,24,29,32,41,57,58,61), we chose cardiac-specific transgenic expression of a dominant inhibitory mutant of Lef-1. The alternative of employing Tcf3/ Tcf4 gene-targeted mice was limited by the early lethality of these models, with Tcf3 Ϫ/Ϫ embryos dying at approximately embryonic day 9.5 (expanded and duplicated axial mesoderm structures [39]) and Tcf4 Ϫ/Ϫ mice dying shortly after birth with a phenotype of complete absence of the stem cell compartment in the crypts of the small intestine (28). Other models were considered, including transgenic expression of inhibitors of Wnt signaling (e.g., secreted frizzled-related proteins or Dickkopf proteins), but these seemed illogical since, as noted, our data suggest that hypertrophic stress-induced stabilization of ␤-catenin is Wnt-independent (21).…”
Section: Discussionmentioning
confidence: 99%
“…The activity of TOPGAL was initially described in the context of developing hair follicles, where it partially overlaps with TCF gene expression patterns, correlates with nuclear b-catenin and is inducible by a misexpressed stabilized form of b-catenin Fuchs, 1999, Merrill et al, 2001;Jamora et al, 2003). The reporter is also active in the primitive streak and node of gastrulating embryos (Merrill et al, 2004;Nakaya et al, 2005), in developing lung epithelia (De Langhe et al, 2005;Shu et al, 2005) and during wound healing in skin (Fathke et al, 2006); in all cases, there is evidence for Wnt signaling in these tissues, if not in all TOPGAL-positive cells.…”
Section: Transgenic Tcf Reporters: a Brief Historymentioning
confidence: 99%
“…In some cases, default repression by TCFs appears to be at least as important as Wnt/TCFmediated activation for proper target gene regulation (e.g., Brannon et al, 1997;Crawford et al, 1999;Yang et al, 2000;Knirr and Frasch, 2001;Merrill et al, 2001;Park et al, 2005). It is quite possible that Wnt signaling events that direct the de-repression of TCF target genes, but that do not trigger robust activation by TCFs, might not be detectable by multimerized TCF reporters, which have a baseline of zero and thus cannot register changes in repression (Merrill et al, 2004).…”
Section: Why Do Vertebrate Tcf Reporters Work?mentioning
confidence: 99%
See 1 more Smart Citation